Enhanced Oxygen Reduction Reaction Via Oxygen Vacancy-Rich Silica-Supported Ag/Pd Nanoshells - dos Santos Pereira, Fellipe; Anchieta e Silva, Felipe; Azevedo Silva, Augusto César; de Jesus Gomes Varela Júnior, Jaldyr; Mateus Pinatti, Ivo; Rojas, Alex; Mantilla, Angeles; Alcântara, Ana C. S.; Baraldi Dourado, Andre Henrique [UNESP]; Tofanello, Aryane; Atsushi Tanaka, Auro; Silva Rodrigues, Thenner; et al. (Wiley, 2024)
Herein, we demonstrated the fine-tuning of catalysts’ active phase by employing AgPd nanoshells with distinct Ag/Pd ratios synthesized via a galvanic replacement method for the oxygen reduction reaction (ORR). However, more interestingly, the subsequent immobilization of such Ag/Pd ratios onto silica further influenced the support characteristics, creating an increasing concentration of oxygen vacancies in this typically inert support — a surprising and unparalleled outcome attested by electrochemical impedance spectroscopy, electron paramagnetic resonance, and theoretical calculation. Such a phenomenon promoted obtaining an optimized electro/photocatalyst with exceptional activity, facilitating not just the ORR but also the photochemical water-splitting reaction. Curiously, adjusting the Ag/Pd ratio also affected the ORR mechanism, which was switched from a 2-electron to a 4-electron after optimization. Finally, Ag38Pd62/SiO2, the catalyst with the best proportion, exhibited a remarkable hydrogen production rate of 1039.8 μmol/gcatalyst during 300 minutes of water splitting, surpassing the performance of the conventional Degussa TiO2 P25 catalyst.
Keywords: AgPd nanoshells; EPR; Oxygen reduction reaction; Oxygen vacancies creation; Photochemical water-splitting; Silica